Self-consistent approach of the constitutive law of a two-phase visco-elastic material described by fractional derivative models - Dinzart, F.; Lipiński, P. (Archives of Mechanics, 2010)
The constitutive law of a two-phase isotropic polymer blending described by fractional derivative models is obtained through a classical self-consistent scheme. A parametric analysis is driven to describe the influence of the four parameters associated with the constitutive law description and to comprise the conditions of application of the model. An identification of the set of parameters is performed by mechanical spectroscopy for two amorphous polymers: the polymethyl methacrylate (PMMA) and the styrene acrylonytrile copolymer (SAN) and their mixture, to evaluate the ability of the model to reproduce the experimental results obtained from the Dynamic Mechanical Thermal Analysis.